CD14 is a key organizer of microglial responses to CNS infection and injury. Issue 4 (18th December 2015) - Janova, Hana; Böttcher, Chotima; Holtman, Inge R.; Regen, Tommy; van Rossum, Denise; Götz, Alexander; Ernst, Anne‐Sophie; Fritsche, Christin; Gertig, Ulla; Saiepour, Nasrin; Gronke, Konrad; Wrzos, Claudia; et al.
Abstract : Microglia, innate immune cells of the CNS, sense infection and damage through overlapping receptor sets. Toll‐like receptor (TLR) 4 recognizes bacterial lipopolysaccharide (LPS) and multiple injury‐associated factors. We show that its co‐receptor CD14 serves three non‐redundant functions in microglia. First, it confers an up to 100‐fold higher LPS sensitivity compared to peripheral macrophages to enable efficient proinflammatory cytokine induction. Second, CD14 prevents excessive responses to massive LPS challenges via an interferon β‐mediated feedback. Third, CD14 is mandatory for microglial reactions to tissue damage‐associated signals. In mice, these functions are essential for balanced CNS responses to bacterial infection, traumatic and ischemic injuries, since CD14 deficiency causes either hypo‐ or hyperinflammation, insufficient or exaggerated immune cell recruitment or worsened stroke outcomes. While CD14 orchestrates functions of TLR4 and related immune receptors, it is itself regulated by TLR and non‐TLR systems to thereby fine‐tune microglial damage‐sensing capacity upon infectious and non‐infectious CNS challenges. GLIA 2016;64:635–649. Main points: CD14 controls microglial sensitivity and responses to LPS in a cell‐specific manner. CD14 prevents excessive CXCL1 production via an IFNβ‐mediated negative feedback. CD14 acts as a mandatory gate keeper for microglial and CNS responses to damage.